2010
DOI: 10.1530/eje-09-0973
|View full text |Cite
|
Sign up to set email alerts
|

Models to predict changes in serum IGF1 and body composition in response to GH replacement therapy in GH-deficient adults

Abstract: Objective: Clinical response to GH therapy in GH-deficient (GHD) adults varies widely. Good predictors of treatment response are lacking. The aim of the study was to develop mathematical models to predict changes in serum IGF1 and body composition (BC) in response to GH therapy in GHD adults. Design and methods: One hundred and sixty-seven GHD patients (103 men, median age 50 years) were studied before and after 12 months of GH treatment. GH dose was tailored according to serum IGF1 concentrations. Good respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 56 publications
3
19
1
Order By: Relevance
“…Previous studies in adult GHD have found an association between the response to GH and clinical and biochemical parameters, such as BMI, age, gender, serum GH-binding protein levels, GH dose, and the route of estrogen replacement in women [31,32]. Recently, Barbosa et al [33] developed mathematical models to predict GH responsiveness and found the clinical predictors of GH therapy were gender, serum insulin, BMI, and body fat at baseline. In the present study, we found that daily dose, IGF-I SD score at baseline and body fat were lower in those who were good responders for IGF-I.…”
Section: Clinical Responsementioning
confidence: 99%
“…Previous studies in adult GHD have found an association between the response to GH and clinical and biochemical parameters, such as BMI, age, gender, serum GH-binding protein levels, GH dose, and the route of estrogen replacement in women [31,32]. Recently, Barbosa et al [33] developed mathematical models to predict GH responsiveness and found the clinical predictors of GH therapy were gender, serum insulin, BMI, and body fat at baseline. In the present study, we found that daily dose, IGF-I SD score at baseline and body fat were lower in those who were good responders for IGF-I.…”
Section: Clinical Responsementioning
confidence: 99%
“…GH replacement therapy improves the metabolic abnormalities, but there is considerable variability in treatment response. Clinical variables, such as sex, age, BMI, GH dose, and the route of estrogen replacement in women have been linked to the response to GH replacement (3, 4, 5), but together these factors only explain a small part of the variability in GH treatment effect (6). Genetic factors, such as polymorphisms in genes within the GH signaling cascade, may also influence the responsiveness to GH.…”
Section: Introductionmentioning
confidence: 99%
“…This has been shown both in randomized placebo-controlled trials (1) and in large-scale observational studies (2,3,4,5,6,7,8,9,10,11,12).…”
Section: Introductionmentioning
confidence: 80%
“…In a previous KIMS analysis by FeldtRasmussen et al, sex, age and baseline IGF1 were predictors of IGF1 response and clinical changes to GHRT (11) In another study, sex was also the best predictor of favourable change in body fat and IGF1 response (9). In these studies, the association of different clinical baseline variables with IGF1 response and changes in clinical outcome variables such as weight, BMI, cholesterol and quality of life or body fat were analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation